Л.БУДАГОВ СӨЗДІГІНДЕГІ ИРАН ТІЛДЕРІНЕН ЕНГЕН СӨЗДЕР (Journal of Oriental Studies, 2016)
В статье рассматриваются слова иранского проис-хождения, приведенные в словаре Будагова.The words came from Iran which are given indictionary of Budagov are considered in this article